Climate change and population aging may impact the benefits of improved air quality on cardiovascular mortality in Guangzhou: epidemiological evidence and policy implications. Issue 2 (26th January 2023) - Wu, Chenguang; Dong, Hang; Ou, Jiajun; Li, Dan; Song, Yuanyuan; Luo, Chunliang; Yu, Zixun; Liang, Boheng; Yu, Yingxin; Qin, Pengzhe; Qi, Zenghua; Cai, Zongwei
Abstract : Dynamic changes in the contribution of air pollution, meteorological conditions and aging to cardiovascular mortality. Abstract : Air pollution is the primary environmental risk factor contributing to global cardiovascular mortality. In China, a series of air pollution control policies launched in 2013 have led to substantial improvements in air quality over the past 10 years. However, the health benefits of improved air quality on cardiovascular mortality remain unclear under the combined effects of climate change and population aging. In this study, we investigated dynamic changes in the contribution of air pollution, meteorological conditions and aging to cardiovascular mortality over 9 years (2013–2021) in Guangzhou, China using generalized additive models and machine learning analysis. Although the air quality in Guangzhou has continuously improved since 2013, cardiovascular mortality has increased since 2019 and approached 2013 levels in 2021. Use of the SHapley Additive exPlanation (SHAP) approach to interpret the model outputs revealed that meteorological factors have gradually replaced air pollutants as the main environmental factors affecting cardiovascular mortality since 2016. Concurrently, the impact of population aging on cardiovascular mortality has increased year-on-year. Our results provide important insights into improved air quality related health benefits that could aid development of an early warning service system and national environmental and public health policy related to climate change and population aging.